Transmisi dan Transformasi Tahfidz Al-Qur’an dan Hadis Di Pondok Pesantren Al-Aqobah 4 - Ahmad Fathurrobbani (Institut Ilmu Keislaman Zainul Hasan Genggong, 2021)
Tahfidz Al-Qur'an has been one of the prima donna in the present era which makes many people memorize it in droves. However, it is inversely proportional to that, amid the proliferation of the Tahfidz Al-Qur'an program, Tahfidz Al-Hadith has received less attention. This is where the Al-Aqobah 4 Islamic Boarding School offers its superior activities, namely Tahfidz Al-Qur'an and Hadith. Because all this time Tahfidz Al-Hadith's activity is still not very boisterous. Therefore, to ease the burden on the students in the memorization process. This research is a study of living Qur'an and Hadith that uses a qualitative approach by directly studying and assessing and participating in the environment in which these concepts are offered. Pondok Pesantren Al-Aqobah 4 which is located in Jombang Regency has time management for scientific transmission so that the Tahfidz Al-Qur'an and Hadith can be well absorbed by the students, and there is a process of scientific transformation of its own for Tahfidz Al-Qur'an and Hadith. in order to complete the scientific transmission process. Of course, this process has its own expectations and realities which the researchers call the model of and the for model. The purpose of this research is to find out this model and the procession to the impact of scientific transmission and transformation on the students who are processing it.